Escherichia coli - Fouch, Sarah (Henry Stewart Talks, 2025)
Clinical manifestation of E. coli, Strains that cause gastrointestinal infection, Epidemiology of E. coli, Virulence factors, Resistance of E. coli, Characterisation of seven strains of E. coli